Gas transport and free volume study in polyethylene based epoxy membranes. (May 2015) - Patil, Pushkar N; Checchetto, R; Ferragut, R; Aghion, S; Miotello, A; Brusa, R S
Abstract: The mechanism of gas diffusivity in amine modified epoxy membranes is studied in the frame of free volume properties. Epoxy membranes with two different crosslinking densities and composite with Graphene nanoplatelets were prepared by solvent casting method. The free volume parameters measured by Positron Annihilation Spectroscopy (PAS) show inverse correlation with crosslinking density of the samples. The gas permeability and diffusivity for CO2 have been studied by gas permeation measurements. The study reveals that the gas permeability and diffusivity change significantly as a function of crosslinking density, free volumes and structural relaxations of the molecular chains.